2020
DOI: 10.1016/j.cell.2020.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Modalities and Implantable Technologies for Neuromodulation

Abstract: Techniques for neuromodulation serve as effective routes to care of patients with many types of challenging conditions. Continued progress in this field of medicine will require (1) improvements in our understanding of the mechanisms of neural control over organ function and (2) advances in technologies for precisely modulating these functions in a programmable manner. This review presents recent research on devices that are relevant to both of these goals, with an emphasis on multimodal operation, miniaturize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
158
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(159 citation statements)
references
References 167 publications
(251 reference statements)
0
158
0
1
Order By: Relevance
“…The basic concept of this approach may be potentially expandable for continuous monitoring of lethal cardiac diseases through chronic implantation of the device and integration with current state-of-the-art means of wirelessly communicating power and data. 39 Methods 4D heart segmentation. All ultrasound images were acquired using the Vevo 3100 small animal ultrasound system (FUJIFILM VisualSonics Inc., Toronto, Canada).…”
Section: Discussionmentioning
confidence: 99%
“…The basic concept of this approach may be potentially expandable for continuous monitoring of lethal cardiac diseases through chronic implantation of the device and integration with current state-of-the-art means of wirelessly communicating power and data. 39 Methods 4D heart segmentation. All ultrasound images were acquired using the Vevo 3100 small animal ultrasound system (FUJIFILM VisualSonics Inc., Toronto, Canada).…”
Section: Discussionmentioning
confidence: 99%
“…[ 113 ] The electrodes exhibit subcellular cross‐sectional dimensions (diameter ≈7 μm) that are an order of magnitude smaller than traditional recording electrodes, resulting in a significantly reduced stiffness of 4540 N m −1 compared with other silicon probes (≈150 kN m −1 with cross‐section dimensions of 15 × 120 μm 2 ) and commercial electrodes for DBS (≈1 MN m −1 with diameters of ≈100 μm). [ 114 ] As a result, they elicit much reduced chronic tissue responses after implantation. In addition, Guitchounts et al demonstrated 16‐channel arrays built from ultrathin (diameter ≈4.5 μm) carbon fiber to record LFPs across multiple cortical regions in birds with negligible immune response.…”
Section: Materials and Devices For Electrical Biointerfacingmentioning
confidence: 99%
“…Model-based reinforcement learning is an enhanced process whereby the computer learns from its trial-and-error experiences to build a model of experiences, adaptations, and results and then uses this model to more efficiently “choose” actions when faced with new situations. Another variation called neuromodulation allows adaptation in a BMI of the input–output sequence programmed when decoding individual neuronal signals; instead of adapting the modeled linkages between signals as with model-based reinforcement learning, the programmed response to each individual signal also changes as the machine learns through experience (Won et al 2020).…”
Section: Integration With Artificial Intelligence (Ai)mentioning
confidence: 99%